2009
DOI: 10.1063/1.3206667
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic evidence of a strain-enhanced ferromagnetic state in LaCoO3 thin films

Abstract: Strain-induced modification of magnetic properties of lightly hole doped epitaxial LaCoO3 thin films on different substrates were studied with variable temperature magnetic force microscopy (MFM). Real space observation at 10 K reveals the formation of the local magnetic clusters on a relaxed film grown on LaAlO3 (001). In contrast, a ferromagnetic ground state has been confirmed for tensile-strained film on SrTiO3 (001), indicating that strain is an important factor in creating the ferromagnetic state. Simult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
53
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 17 publications
4
53
0
Order By: Relevance
“…In our previous work, using local spin density approximation combined with the Hubbard U correction (LSDA+U), we have shown that a ferromagnetic state based on a homogenous intermediate spin (IS) state (S=1) can be stabilized above 3.8% tensile strain [10]. The ferromagnetic IS state is, however, inconsistent with two experimentally determined properties of strained LCO: the IS state is half-metallic while experiment shows that strained LCO is insulating [7], and a rather high critical strain of 3.8% is required, which is somewhat higher than that in experiment (~2%) [5][6][7][8][9][10]. Most recently, using a LDA+U approach, Hsu et al have shown that a HS/LS mixed state has a lower energy than that of the IS state in tensile-strained LCO on STO [28].…”
Section: Introductionmentioning
confidence: 59%
See 1 more Smart Citation
“…In our previous work, using local spin density approximation combined with the Hubbard U correction (LSDA+U), we have shown that a ferromagnetic state based on a homogenous intermediate spin (IS) state (S=1) can be stabilized above 3.8% tensile strain [10]. The ferromagnetic IS state is, however, inconsistent with two experimentally determined properties of strained LCO: the IS state is half-metallic while experiment shows that strained LCO is insulating [7], and a rather high critical strain of 3.8% is required, which is somewhat higher than that in experiment (~2%) [5][6][7][8][9][10]. Most recently, using a LDA+U approach, Hsu et al have shown that a HS/LS mixed state has a lower energy than that of the IS state in tensile-strained LCO on STO [28].…”
Section: Introductionmentioning
confidence: 59%
“…Furthermore, strain engineering in these oxide heterostructures opens up routes for creating novel electronic phases [2][3][4]. An exciting example is the recent demonstration of biaxial tensile strain stabilizing an insulating ferromagnetic (FM) ground state in LaCoO 3 (LCO) [5][6][7][8][9][10][11][12][13][14]. Though LCO is a classic example of a correlated 3d transition metal perovskite oxide [15,16], FM correlation has never been observed for the bulk ground state where the Co 3+ ions exist in the so-called low spin (LS) state (total spin per Co S=0) [15].…”
Section: Introductionmentioning
confidence: 99%
“…Regions close to the interfaces or surfaces develop ferromagnetic order at low temperature. Recent work has shown the importance of extended states [6] in LCO bulk particles, a FM phase transition in LCO at T c ≈ 87 K, and another transition near T o ≈ 40 K. [5] These behaviors, as well as others reported for bulk and nanoparticle powders and thin films, [14][15][16][17] are consistent with a particle core-interface model that includes, for particles larger than ≈ 20 nm, a core region exhibiting a crossover between two types of paramagnetism near T o , and an interface region located near surfaces or interfaces with impurity phases. Tensile stress, either from the lattice mismatch between the interfaces and the core, or between the particle surface and the core, can induce a FM transition in the interface region below T c .…”
Section: Magnetometrymentioning
confidence: 99%
“…13 In these studies, the authors demonstrate that the different oxygen vacancy content of the films grown on the two different substrates can account for the enhancement of the magnetic properties. While some 9,10 have cited chemical inhomogeneity as the cause of the long-range ferromagnetic order in epitaxial LCO films, an explanation of how these defects could be responsible for the stabilization of a long-range ferromagnetic ground state is still lacking. Recent work has presented the possibility of added complexity due to the possibility of ferroelastic behavior coupling to the strain dependent magnetism in these films.…”
mentioning
confidence: 99%